Optical aberrations and vector beams as a tool for hollow structured light generation - Sulc Miroslav; Gayde Jean-Christophe; Polak Krystof (EPJ Web of Conferences)
A method for the generation of structured laser beams (SLB) and hollow structured laser beams (HSLB) whose transverse profiles are invariant and can propagate to infinity is described. SLBs are formed after passing through an optical system that generates a special wavefront as a combination of rotationally symmetric optical aberrations. Transverse profile consists of concentric circles with a very bright central core and a bounding outer-ring. The divergence of the central core 0.01 mrad has been experimentally confirmed. When the system was illuminated with a special vector beam, a hollow SLB (HSLB) beam was generated. Its central part is very narrow and completely dark. Unlike conventional hollow beams, where the electric field is zero in the dark areas, an electromagnetic field with the zero Poynting vector is present in this part of the beam. By varying the illumination parameters of the vector beam, it is possible to obtain situations where there is a longitudinal component of the electric field or/and magnetic field in the central core. The simulation results are in good agreement with the SLB profile measurements using a polarization camera.